Phase 1b/2a study of galunisertib, a small molecule inhibitor of transforming growth factor-beta receptor I, in combination with standard temozolomide-based radiochemotherapy in patients with newly diagnosed malignant glioma - Wick, Antje; Desjardins, Annick; Suárez García, Cristina; Forsyth, Peter; Gueorguieva, Ivelina; Burkholder, Tiana; Cleverly, Ann Louise; Estrem, Shawn T.; Wang, Shuaicheng; Lahn, Michael M.; Guba, Susan C.; Capper, David; et al. (Investigational new drugs, 2020)
Purpose Galunisertib, a TGF-β inhibitor, has demonstrated antitumor effects in preclinical and radiographic responses in some patients with malignant glioma. This Phase 1b/2a trial investigated the clinical benefit of combining galunisertib with temozolomide-based radiochemotherapy (TMZ/RTX) in patients with newly diagnosed malignant glioma (NCT01220271). Methods This is an open-label, 2-arm Phase 1b/2a study (N = 56) of galunisertib (intermittent dosing: 14 days on/14 days off per cycle of 28 days) in combination with TMZ/RTX (n = 40), versus a control arm (TMZ/RTX, n = 16). The primary objective of Phase 1b was to determine the safe and tolerable Phase 2 dose of galunisertib. The primary objective of Phase 2a was to confirm the tolerability and pharmacodynamic profile of galunisertib with TMZ/RTX, and the secondary objectives included determining the efficacy and pharmacokinetic (PK) profile of galunisertib with TMZ/RTX in patients with glioblastoma. This study also characterized the changes in the major T-cell subsets during TMZ/RTX plus galunisertib treatment. Results In the Phase 2a study, efficacy results for patients treated with galunisertib plus TMZ/RTX or TMZ/RTX were: median overall survival (18.2 vs 17.9 months), median progression-free survival (7.6 vs 11.5 months), and disease control rate (80% [32/40] vs 56% [9/16] patients) respectively. PK profile of galunisertib plus TMZ/RTX regimen was consistent with previously published PK data of galunisertib. The overall safety profile across treatment arms was comparable. Conclusion No differences in efficacy, safety or pharmacokinetic variables were observed between the two treatment arms.
Gesehen am 18.11.2021